Strategic Pathways for Competitive Advantage in Recycled Aluminium: An Integrated AHP-SWOT Analysis - Waraney Daniel Carl Mumbunan; Nimmi Zulbainarni; Suhendi (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The recycled aluminium industry faces competitive challenges that require effective strategies to enhance industry competitiveness. This study aims to analyze internal and external factors within a company and prioritize strategies to improve performance and sustainability. The objectives are to evaluate the company’s strengths, weaknesses, opportunities, and threats, and to identify key strategies that support competitive advantage. Data was collected from October 2024 to December 2024 using both qualitative and quantitative methods from 7 respondents. The analysis involved several steps, including IFE analysis (Strengths & Weaknesses) and EFE analysis (Opportunities & Threats) to determine factor priorities, formulation of the TOWS-SWOT matrix, and evaluation of strategy priorities using AHP-SWOT analysis. Based on the TOWS-SWOT matrix, 12 strategies were developed, with ST3, ST2, and WO3 identified as the top priorities. This study provides comprehensive insights into companies in determining competitive and sustainable strategy alternatives in the recycled aluminium industry, which can ultimately enhance industry competitiveness and support long-term sustainability.